2020
DOI: 10.3390/en13061366
|View full text |Cite
|
Sign up to set email alerts
|

Impurity Effects on the Mechanical Properties and Permeability Characteristics of Salt Rock

Abstract: Impure salt rock strata are extensively distributed in China, giving them great significance in the study of the physical properties of impure salt rock for the construction of underground gas storage in salt mines. To investigate the confining pressure and impurity effects on the mechanical properties and gas permeability characteristics of salt rock, permeability tests under hydrostatic confining pressure and conventional triaxial compression (CTC), on salt rock samples with different impurity contents, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…However, torsional deformation experiments on halite‐calcite mixtures demonstrated that the strength of the two‐phase mixtures was higher than pure halite, and that the calcite grains hindered halite plastic flow and stress relaxation (Marques et al, 2010). Moreover, another study on the mechanical properties and gas permeability of rock salt showed that the impurity content results in an increase of the rock salt strength, and a higher permeability (Zhang, Liu, et al, 2020).…”
Section: Impact Of Geochemical and Microstructural Characteristics On...mentioning
confidence: 99%
“…However, torsional deformation experiments on halite‐calcite mixtures demonstrated that the strength of the two‐phase mixtures was higher than pure halite, and that the calcite grains hindered halite plastic flow and stress relaxation (Marques et al, 2010). Moreover, another study on the mechanical properties and gas permeability of rock salt showed that the impurity content results in an increase of the rock salt strength, and a higher permeability (Zhang, Liu, et al, 2020).…”
Section: Impact Of Geochemical and Microstructural Characteristics On...mentioning
confidence: 99%
“…In recent years, the permeability problems of various engineering rocks have been experimentally studied by many scholars. Because the stress of rocks in deep underground engineering is frequently a dynamic load that changes over time, based on triaxial compression tests and triaxial cyclic loading tests, scholars have performed a lot of research on various types of rocks in terms of permeability characteristics, and obtained the deformation, strength, and permeability evolution laws of different rocks [9][10][11][12][13][14][15]. By analyzing the seepage-stress coupling mechanism of sandstone under different confining pressures, the variation law of permeability with a stress-strain curve was obtained, finding that permeability is a function of axial stress and strain [16][17][18][19], and the permeability in different deformation stages of sandstone shows different characteristics [20].…”
Section: Introductionmentioning
confidence: 99%
“…Amalia et al [35] simulated CO 2 injection into sandstone and explored relative permeability characteristics for CO 2 in sandstone under normal temperature and overburden pressure. Zhang et al [36] held that the permeability of salt rock with different components rose with the increase in pore pressure and was affected by the Klinkenberg effect. Al-Khdheeawi et al [37,38] studied the effects of rock properties on geochemical reactivity and CO 2 storage efficiency and the effects of CO 2 injection on permeability.…”
Section: Introductionmentioning
confidence: 99%